2019
DOI: 10.3390/ijerph16193559
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Evidence of Metal-Driven Anaerobic Oxidation of Methane in the Shenhu Area, the South China Sea

Abstract: Anaerobic oxidation of methane (AOM) is a common biochemical process in the ocean and it plays an important role in global climate change, elemental circulation, and atmospheric evolution over geological time. In this paper, we analyzed of δ34S, Fe, Mn, Ca/Ti, and Sr/Ti ratios, and the date of carbon and sulfur from the site SH3 of Shenhu area. Result showed that (1) 0–6 mbsf (meter blow the sea floor) was mainly affected by OSR (anaerobic oxidation of organic matters) and 7–15 mbsf was a paleo-SMTZ (sulfate–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…As such, the combined study of authigenic carbonates and associated CWCs in seep environments is potentially useful to calibrate the geochemical signatures within authigenic carbonates to aid in reconstruction of past conditions (Figure 8). In addition, U-Th dating of authigenic carbonates is a powerful tool that can also contribute to our understanding of the geological factors and processes controlling seabed methane release [86][87][88][89][90][91]. However, accurate dating of authigenic carbonates is difficult owing to contamination by detrital terrestrial material [84].…”
Section: Cwc Trace-element Contentsmentioning
confidence: 99%
“…As such, the combined study of authigenic carbonates and associated CWCs in seep environments is potentially useful to calibrate the geochemical signatures within authigenic carbonates to aid in reconstruction of past conditions (Figure 8). In addition, U-Th dating of authigenic carbonates is a powerful tool that can also contribute to our understanding of the geological factors and processes controlling seabed methane release [86][87][88][89][90][91]. However, accurate dating of authigenic carbonates is difficult owing to contamination by detrital terrestrial material [84].…”
Section: Cwc Trace-element Contentsmentioning
confidence: 99%
“…As mentioned above, the∑REE/Ti increases abruptly at sites SH1 and SH3 at 25 mbsf and 17 mbsf, respectively (Figure 5). However, the sulfate and methane transition zone (SMTZ) is at 27-36 msbf of site SH1 and the SMTZ at 18-25 mbsf of site SH3 [15,16,24]. The results show that the ∑REE/Ti increased above the SMTZ.…”
Section: The Influence Of Aom On the Enrichment Of Rees Reementioning
confidence: 92%
“…At the same time, most of the metal oxides will convert to metal sulfide in the presence of excess hydrogen sulfide [2,3,70]. With the deepening of research, metal-driven anaerobic oxidation of methane (MD-AOM) is found at the bottom of the SMTZ worldwide [15,24,38,71]. During the metal-driven anaerobic oxidation of methane 9 Geofluids (MD-AOM), more metal oxides are converted to metal sulfides compared to the SD-AOM.…”
Section: The Enrichment Mechanism Of Ree Influenced By Aommentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic oxidation of methane (AOM) reactions is another signature of hydrate distribution in marine sediment, as it especially active in the sediments where gas hydrate is underlying. 57 A one-dimensional (1D) numerical model applied to investigate the distribution of advective methane flux with the AOM process in GHBS of the Shenhu area, SCS, which also indirectly proves the distribution of methane hydrate in this area. 58 Geochemical analysis of sediments from the Shenhu area, SCS indicated the geochemical diagenetic response to the occurrence of AOM, and it suggests that strong AOM can be beneficial to methane accumulation for hydrate formation in GHSZ.…”
Section: Coring Techniquesmentioning
confidence: 99%